2017
DOI: 10.1155/2017/7063859
|View full text |Cite
|
Sign up to set email alerts
|

Yin-Cold or Yang-Heat Syndrome Type of Traditional Chinese Medicine Was Associated with the Epidermal Growth Factor Receptor Gene Status in Non‐Small Cell Lung Cancer Patients: Confirmation of a TCM Concept

Abstract: Traditional Chinese Medicine (TCM) therapies should be tailored according to the different syndrome types. In order to identify the relationship between the TCM Yin-cold (YC) or Yang-heat (YH) syndrome types and the EGFR gene status, we prospectively studied 310 NSCLC patients. TCM YH or YC was diagnosed by three TCM experts. TCM symptoms and signs were entered into a binary cluster analysis. The relationships between the EGFR gene status, YH or YC syndrome types, and classification by cluster analysis were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…The Yang group feels hot or has hot flashes, sweats during daily activities, and prefers cool environments and cold beverages and food. The Yin group feels cold or has cold flashes, does not sweat even during strenuous exercise, and prefers warm environments and hot beverages and food ( 18 ). We also confirmed that matched healthy control subjects had no somatic symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The Yang group feels hot or has hot flashes, sweats during daily activities, and prefers cool environments and cold beverages and food. The Yin group feels cold or has cold flashes, does not sweat even during strenuous exercise, and prefers warm environments and hot beverages and food ( 18 ). We also confirmed that matched healthy control subjects had no somatic symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the warming-yang or cooling-heat should be the guide of treatment principle outline 5 . We have demonstrated that EGFR gene mutated NSCLC patients are more likely with YC syndrome type 6 . Besides, the most common side effect of EGFR-TKIs was red acneiform rashes [7][8][9][10][11] , with thirsty, red and dry tongue and yellow tongue coating, which are typical symptoms and signs for YH syndrome type.…”
Section: Tcm Therapies Have Been Widely Used In Cancer Including Nscmentioning
confidence: 81%
“…Evidence-Based Complementary and Alternative Medicine in mice [40]. Zhu et al indicate that the EGFR status is independently correlated with TCM treatment in non-smallcell lung cancer patients [41]. Although previous study has confirmed the relation between EGFR expression and TCM active compounds using cell membrane chromatography [42], the effect of Xihuang pill on EGFR expression in liver cancer is still unclear.…”
Section: Discussionmentioning
confidence: 99%